Risk Assessment of Severe Congenital Anomalies of the Kidney and Urinary Tract (CAKUT): A Birth Cohort - Katsoufis, Chryso P.; DeFreitas, Marissa J.; Infante, Juan C.; Castellan, Miguel; Cano, Teresa; Safina Vaccaro, Daniela; Seeherunvong, Wacharee; Chandar, Jayanthi J.; Abitbol, Carolyn L. (Frontiers in Pediatrics, 2019)
Recent advances in the early diagnosis of fetal CAKUT with an increase in fetal surgical interventions have led to a growing number of neonatal survivors born with severe renal dysfunction. This, in turn, has required the development of multi-disciplinary treatment paradigms in the individualized management of these infants with advanced stage kidney disease from birth. Early multi-modal management includes neonatal surgical interventions directed towards establishing adequate urine flow, respiratory support with the assessment of pulmonary hypoplasia, and establishing metabolic control to avoid the need for dialysis intervention. The development of specialized imaging to assess for residual renal mass with non-invasive 3-dimensional techniques are rapidly evolving. The use of non-radioactive imaging offers improved safety and allows for early prognostic-based planning including anticipatory guidance for progression to end stage renal disease (ESRD). The trajectory of kidney function during the neonatal period as determined by peak and nadir serum creatinine (SCr) and cystatin C (CysC) during the first months of life provides a guide towards individualized prospective management. This is a single center experience based on a birth cohort of 42 subjects followed prospectively from birth for an average of 6.1±2.8 years at the University of Miami/Holtz Children’s Hospital during the past decade. There was an 8:1 male: female ratio. The birth cohort was divided into 3 subgroups according to CKD Stages at the current age: CKD 1-2 (Group 1) (eGFR >90 ≤60 ml/min/1.73m2) (N=15), CKD stage 3-5 (Group 2) (eGFR ≤59 ml/min/1.73m2) (N=12), and ESRD – Dialysis and/or Transplantation (Group 3) (N=15). A neonatal CysC >3.0 mg/L predicted progression to ESRD while a nadir SCr >0.6 mg/dL predicted progression to CKD 3-5 with the highest specificity and sensitivity by ROC-AUC analysis (P<0.0001). Medical management was directed towards nutritional support with novel formula designs, early introduction of growth hormone and strict control of mineral bone disorder. One of the central aspects of the management was to avoid dialysis for as long as feasible with a primary goal towards pre-emptive transplantation.